Effect of Lanreotide Depot/Autogel on Urinary 5-Hydroxyindoleacetic Acid and Plasma Chromogranin A Biomarkers in Nonfunctional Metastatic Enteropancreatic Neuroendocrine Tumors - Pavel, Marianne Ellen; Phan, Alexandria T.; Wolin, Edward M.; Mirakhur, Beloo; Liyanage, Nilani; Pitman Lowenthal, Susan; Fisher, George A.; Vinik, Aaron I. (Oncologist, 2019)
Background: Urinary 5-hydroxyindoleacetic acid (5-HIAA) is an established biomarker in neuroendocrine tumors and carcinoid syndrome; however, its role in nonfunctional neuroendocrine tumors is not defined. We present post hoc data on urinary 5-HIAA and plasma chromogranin A (CgA) from the CLARINET study. Methods: Patients with well- or moderately differentiated, nonfunctioning, locally advanced or metastatic enteropancreatic neuroendocrine tumors were randomized to deep subcutaneous lanreotide depot/autogel 120 mg or placebo once every 28 days for 96 weeks. Tumor response, evaluated centrally (RECIST 1.0), and progression-free survival (PFS) were assessed by treatment and biochemical response, defined as (a) baseline >upper limit of normal (ULN, 41.6 μmol per day 5-HIAA; 98.1 μg/L CgA) and (b) ≥50% decrease from baseline and to ≤ULN value on study. Results: Forty-eight percent (82 of 171; lanreotide, n = 45; placebo, n = 37) and 66% (129 of 195; lanreotide, n = 65; placebo, n = 64) of randomized patients had 5-HIAA and CgA > ULN at baseline. Among patients with >ULN baseline values who did not progress after 96 weeks of treatment, significantly greater reductions in 5-HIAA and CgA were observed in lanreotide-treated versus placebo-treated patients throughout the study (all p <.05). PFS was significantly prolonged among 5-HIAA responders versus nonresponders (median not reached vs. 16.2 months, p <.0001; hazard ratio [HR] = 0.21, 95% confidence interval [CI], 0.09–0.48) and CgA responders versus nonresponders (median not reached vs. 16.2 months, p =.0070; HR = 0.30, 95% CI, 0.12–0.76), regardless of treatment arm. PFS was also significantly prolonged among lanreotide-treated 5-HIAA responders versus nonresponders (p =.0071) but was not significantly different among placebo-treated 5-HIAA responders versus nonresponders. There were no significant differences in PFS between lanreotide-treated CgA responders versus nonresponders or between placebo-treated CgA responders versus nonresponders. Conclusions: The 5-HIAA findings are noteworthy because they occurred in patients with nonfunctioning enteropancreatic neuroendocrine tumors. Monitoring 5-HIAA and CgA may be useful when treating patients with nonfunctional neuroendocrine tumors. Implications for Practice: Current guidelines focus only on the monitoring of 5-hydroxyindoleacetic acid (5-HIAA) in the diagnosis and management of functional neuroendocrine tumors with carcinoid syndrome. The current post hoc analysis of patients with nonfunctional enteropancreatic neuroendocrine tumors in the CLARINET study demonstrated that measuring and following both 5-HIAA and chromogranin A as biomarkers of disease progression may be useful in the management of patients with nonfunctional neuroendocrine tumors.
CRIS-Team Scopus Importer:2019-05-02
Keywords: 5-Hydroxyindoleacetic acid; Lanreotide; Neuroendocrine tumor; Plasma chromogranin A